The intersection : where evidence based nursing and information literacy meet - Phelps, Sue F.; Hyde, Loree; Wolf, Julie Planchon (Chandos information professional series., 2018)
The Intersection: Where Evidence Based Nursing and Information Literacy Meet describes how the Association of College and Research Libraries (ACRL) Framework and Information literacy Competency Standards for Nursing mesh with nursing essentials, thus speaking to the information needs of nurses, nurse educators, and librarians who support worldwide nursing programs. In order to find the best evidence from studies, students and practicing nurses must be proficient in the entire range of information literacy skills. Though the references for this document are from U.S. organizations, they are applicable to nursing audiences across the globe.